Toll-Like Receptor 3 in Solid Cancer and Therapy Resistance - Muresan, Ximena Maria; Bouchal, Jan; Culig, Zoran; Souček, Karel (Cancers, 2020)
Toll-like receptor 3 (TLR3) is a member of the TLR family, which has been extensively studied for its antiviral function. It is highly expressed in the endosomes of antigen-presenting immune cells and epithelial cells. TLR3 binds specifically double-strand RNAs (dsRNAs), leading to the activation of mainly two downstream pathways: the phosphorylation of IRF3, with subsequent production of type I interferon, and the activation of NF-κB, which drives the production of inflammatory cytokines and chemokines. Several studies have demonstrated TLR3 expression in multiple neoplasia types including breast, prostate, and lung cancer. Most studies were focused on the beneficial role of TLR3 activation in tumor cells, which leads to the production of cytotoxic cytokines and interferons and promotes caspase-dependent apoptosis. Indeed, ligands of this receptor were proposed for the treatment of cancer, also in combination with conventional chemotherapy. In contrast to these findings, recent evidence showed a link between TLR3 and tumor progression, metastasis, and therapy resistance. In the present review, we summarize the current knowledge of the mechanisms through which TLR3 can either lead to tumor regression or promote carcinogenesis as well as the potential of TLR-based therapies in resistant cancer.
Keywords: cytokines; toll-like receptor 3; therapy resistance; metastasis; dsRNA